PROSPECTS FOR INCREASING THE RESOURCE POTENTIAL OF MINERAL RADON WATERS IN THE VINNYTSKA REGION - SHARIKOV, Sergii; CHOMKO, Dmitro (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Background. Prospects for increasing the mineral resource base of Ukraine are one of the main strategies for the development of our country today and in the post-war period. At present, increasing the number of total approved reserves of mineral radon waters by opening new deposits is not a priority component, as it is costly. However, a detailed analysis of the possible increase in the number of operational reserves based on already explored deposits is promising. This work refers to one of the components of the plan for achieving a common better future approved by the members of the United Nations in 2015 (17 sustainable development goals). The material presented in the article refers to point 3, namely – Ensuring a healthy lifestyle and promoting well-being for all at any age. Radon mineral waters are balneological underground waters that have healing properties when used internally or externally. An important factor during the exploitation of such groundwater is their compliance with the conditions, i.e. the established maximum permissible concentrations (hereinafter referred to as MPC), which are in force at the present time. At different periods of time, various stages of exploration of mineral radon waters were carried out within the Vinnytsia region, from exploratory work to detailed exploration. Therefore, a detailed analysis of existing deposits, an assessment of the prospects for expanding or increasing operational reserves, and determining the resource potential of institutions specializing in radon groundwater are important tasks.Methods. This study was conducted on the basis of a detailed analysis of stock materials and a comparison of the actual results of the content of radon mineral waters with other deposits within the Vinnytsia region.Results. As a result of the conducted studies, it was found that within the Resort area, which is located in the city of Nemyriv, there is a potential to increase the operational reserves of mineral radon waters. This statement is based on the analysis of data from the preliminary (1985) and detailed (2004) exploration.Conclusions. Studies have shown that an increase in the operational reserves of mineral radon waters is possible due to the inactive (at the moment) operational well No.6-R. During a detailed assessment of operational reserves, this well was excluded from the calculation of reserves due to the excess of nitrate content (>65 mg/dm3) according to the Industry Standard of Ukraine (GSTU) 42.10-02-96 "Medical mineral waters. Technical conditions". However, the increased nitrate content is not the result of contamination of the target aquifer, but is a consequence of water radiolysis. More detailed studies of this problem could lead to the improvement of the current regulatory requirements for mineral waters specifically for external use.
Keywords: radon; mineral radon groundwater; deposit; reserves; groundwater quality